Comparative Analysis of Financial Performance Before and After Mergers and Acquisitions in Companies Listed on the Indonesia Stock Exchange - Dahlia Pinem; Munasiron Miftah; Bernadin Dwi; Marlina; Nani Ariani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of This study will look at the variations in financial performance between businesses before and after mergers and acquisitions in businesses listed on the Indonesia Stock Exchange during the period of 2019-2021. The sample size used in this research is 18 companies selected through purposive sampling approach. The analysis techniques employed are the Wilcoxon Signed-Rank Test and the Paired Sample t-Test. Liquidity, solvency, and profitability are used as variables in this research. The results of this study show that that there are no significant differences in the current ratio, debt to equity ratio, and return on equity of companies before and after the merger and acquisition